Studi Kasus Mengenai Strategi Belajar Pada Mahasiswa Yang Aktif Dalam Organisasi BEM FIS UNJ - Elisabeth Kewa Making; Fadia Tuffahati; Ryan Fathurrahman Baihaqqi (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study was to find out what strategies were used by students who were active in the UNJ FIS Student Executive Body (BEM) organization. This research was conducted by making a questionnaire which would be answered by students who were active in the UNJ BEM FIS organization. The analytical method used in this study is a qualitative method with a questionnaire model. The results of the study stated that most of them had a good schedule and regular time and some admitted that they sometimes had difficulty managing time. From the results of this study, the average learning strategy they used was to compare priority scales and do the most prioritized things first.